Peningkatan Literasi Hukum Pidana Perlindungan Konsumen bagi UMKM Pemula di Desa Puday, Kabupaten Konawe: Analisis Efektivitas Melalui N-Gain Score: Pengabdian - Lade Sirjon; Arfa; Yan Fathahillah Purnama; La Patuju; La Ode Muhammad Kaisar Demaq; Wahyu Aliansyah; Muhamad Syukri; La Ode Muhammad Ichsan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community engagement program aimed to enhance criminal law literacy regarding consumer protection among beginner micro, small, and medium enterprises (MSMEs) in Puday Village, Konawe Regency. The initiative addressed the significant lack of understanding related to the obligations and risks stipulated under Indonesian consumer protection law, particularly the principles of strict product liability as regulated in the Consumer Protection Act (UUPK). The intervention was structured using a Community Action Research approach, combining direct educational sessions, pre- and post-tests, and participatory discussions to evaluate cognitive and affective changes among participants. Quantitative results revealed a substantial improvement in knowledge, with the average N-Gain Score reaching the “high” effectiveness category (0.75), indicating a strong increase in legal literacy and risk mitigation capabilities. Qualitatively, participants showed not only theoretical advancement but also a motivational shift toward implementing best practices in legal compliance, such as improving product information, service standards, and initial steps toward business legality. The program’s holistic model demonstrates the effective transfer of complex legal concepts into practical solutions and highlights the university’s role in supporting local MSMEs’ resilience.